A Critical Review of Gender Differences in Online Shopping - Amin, Prashant D.; Amin, Bijal (Indian Journal of Marketing, 2010)
The position of women in a modern society is one of the true indexes of its cultural and spiritual attainments. It is women only who would make the difference for the transformation of developing countries like India. The traditional Indian woman too has undergone a metamorphic change in her roles and status, both at workplace and at home coupled with changes in technologies causing women empowerment in economic, social, and political walks of lives (Raja Ramchandran, 2000). To illustrate, the case before us is that of rise of Information Technology [IT]. Although, the Internet has penetrated almost every aspect of everyday life, the current reporting of data on the Internet and gender does not adequately capture the cultural and changing differences in gender roles, and provide a partial view of some of the differences in ways men and women use the Internet (Ruby Roy Dholkiya and others, 2003).